Rethinking Human Development Based on Ar Ra’d Verse 11: How Can Preferences Influence Human Development? - An'im Kafabih; Muhammad Dandy Alif Wildana (AL-MUZARA'AH, 2022)
As human is the centre of development process, it is important to consider preferences of human behavior whether they prefer to change themselves or not. This explanation is inspired by Qur’an surah Ar Ra’d verse 11 that can be interpreted as the set of preferences which might influence someone’s state of condition. However, human development index which is widely used indicator for development study do not consider preference as the main factor of development. Therefore aim of this study is to examine interpretation of that surah whether set of preferences that consist of trust, altruism, patience, risk taking, and negative reciprocity, can influence the state of human development. This research Uses Linear Probability Model (LPM) which is estimated by OLS with 76 countries as observation. The result shows that altruism, patience and risk taking can influence human development significantly, whereas trust and negative reciprocity are not significant. Trust is not significant because there might be a condition of distrust economic activities, rather than trust, that signaled by complete contractual arrangement, whereas non significant of negative reciprocity might because the costly punishment opportunity to punish someone as the form of negative reciprocity, therefore people that think rationally will not take the revenge to others.